3(x+4)^2 -6=8
3(x+4)^2 = 14
(x+4)^2 = 14/3
x+ 4 = +- sqrt (14/3)
x= -4 + sqrt(14/3) or x= -4 - sqrt(14/3) !
2006-11-08 07:36:44
·
answer #1
·
answered by Anonymous
·
1⤊
2⤋
Start by adding 6 to both sides to get:3(x+4)^2=14. Next, divide both sides by 3 to get:(x+4)^2=14/3. Now take the square root of both sides to get: x+4=plus or minus sqrt(14/3). Finally, subtract four from both sides to get: x=-2 +-sqrt(14/3).
2006-11-08 15:38:36
·
answer #2
·
answered by bruinfan 7
·
0⤊
1⤋
11
2006-11-08 15:38:18
·
answer #3
·
answered by Anonymous
·
0⤊
1⤋
take it step by step.
first take -6 to the other side and add it to 8, 3(x+4)^2=8+14
then divide both sides by 3 to give (x+4)^2=14/3
now take the under root of both sides to give x+4=root(14/3)
solve the root x+4=2.16
take 4 to the other side to give x=-1.84
2006-11-08 15:46:47
·
answer #4
·
answered by freewonderingsoul 1
·
0⤊
0⤋
3(x+4)^2=14
(x+4)^2=14/3
(x+4)=+-Sqrt[14/3]
x=-4+-Sqrt[14/3]
2006-11-08 15:38:22
·
answer #5
·
answered by Greg G 5
·
0⤊
0⤋
multiply out the brackets and bring real numbers to other side from 3x^2 etc
2006-11-08 15:40:14
·
answer #6
·
answered by Anonymous
·
0⤊
1⤋
3(x+4)^2 -6=8
3(x^2+8x+16)-6-8=0
3x^2+24x+48-6-8=0
3x^2+24x+34=0
x=(-24+/-â24^2-4*3*34)/6
x=-4+/-(1/6)â576-408
x=-4+/-(1/6)â168=-4+/-(1/3)â42
x=.3205
x=-5.840
2006-11-08 15:43:09
·
answer #7
·
answered by yupchagee 7
·
0⤊
0⤋